MODEL DISCOVERY LEARNING BERBANTUAN MIND MAP UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA DI KELAS X IPS 2 SMA NEGERI 1 PONTIANAK - Wijaya, Tri; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research started from the concerns of sociology teachers regarding the low skills of students? critical thinking. The research aims to know if sociology learning activities through discovery learning assisted with mind map done by teachers can improve critical thinking skills of class X IPS 2 students of SMA Negeri 1 Pontianak. The method used in this study is Classroom Action Research (CAR), referring to Kurt Lewin?s approach in which the action research is viewed as a cycle of planning, action, observation, and reflection. The research was conducted collaboratively by the researcher and the teachers of sociology subject in three cycles, in which each cycle comprises of two times action. The result showed that on the first cycle, the students? critical thinking skills were on relatively medium achievement category with a mean score of 65,57; the second cycle indicates a higher achievement category at mean score 73,78, and on the third cycle the result improved to be relatively very high achievement category with mean score 81,57. It is concluded that there is an improvement in students? critical thinking skills through discovery learning assisted with mind map in sociology learning in class X IPS 2 of SMA Negeri 1 Pontianak.  Keywords: Critical Thinking Skills, Discovery Learning, Mind Map, Sociology Learning